Multipronged Attack of Stem Cell Therapy in Treating the Neurological and Neuropsychiatric Symptoms of Epilepsy - Sadanandan, Nadia; Saft, Madeline; Gonzales-Portillo, Bella; Borlongan, Cesar V. (Frontiers in Pharmacology, 2021)
Epilepsy stands as a life-threatening disease that is characterized by unprovoked seizures. However, an important characteristic of epilepsy that needs to be examined is the neuropsychiatric aspect. Epileptic patients endure aggression, depression, and other psychiatric illnesses. Therapies for epilepsy can be divided into two categories: antiepileptic medications and surgical resection. Antiepileptic drugs are used to attenuate heightened neuronal firing and to lessen seizure frequency. Alternatively, surgery can also be conducted to physically cut out the area of the brain that is assumed to be the root cause for the anomalous firing that triggers seizures. While both treatments serve as viable approaches that aim to regulate seizures and ameliorate the neurological detriments spurred by epilepsy, they do not serve to directly counteract epilepsy’s neuropsychiatric traits. To address this concern, a potential new treatment involves the use of stem cells. Stem cell therapy has been employed in experimental models of neurological maladies, such as Parkinson’s disease, and neuropsychiatric illnesses like depression. Cell-based treatments for epilepsy utilizing stem cells such as neural stem cells (NSCs), mesenchymal stem cells (MSCs), and interneuron grafts have been explored in preclinical and clinical settings, highlighting both the acute and chronic stages of epilepsy. However, it is difficult to create an animal model to capitalize on all the components of epilepsy due to the challenges in delineating the neuropsychiatric aspect. Therefore, further preclinical investigation into the safety and efficacy of stem cell therapy in addressing both the neurological and the neuropsychiatric components of epilepsy is warranted in order to optimize cell dosage, delivery, and timing of cell transplantation.